Limulus in the Limelight A Species 350 Million Years in the Making and in Peril? - Tanacredi, John T. (Springer US, 2001)
Limulus in the Limelight: A Species 350 Million Years in the Making and in Peril? contains 14 chapters covering the horseshoe crab's biology, ecology and evolutionary development. The book is a result of three mini-conferences held between 1996 and 2000 celebrating the populations in NY harbor. This book exposes the impacts of over fishing on this species; clarifies the future research agenda for the species worldwide and emphasizes the need for conservation of this fascinating creature's estuaries/ocean habitats. Biologists, ecologists, science educators, and conservationists will welcome this book because it is aimed at the preservation of Limulus, not only for its pharmacological interest but for the mystery related to its longevity. Limulus is a unique animal which has provided numerous uses for man over the years, from fertilizer to bait to medical research. However, if this species is not protected soon, it will be lost for the future.